Analysis and numerical simulation of a supercell tornado at the Hong Kong adjacent waters. (23rd March 2022) - Chan, P. W.; Hon, K. K.; Robinson, P.; Kosiba, K.; Wurman, J.; Li, Q. S.
Abstract: A tornado/waterspout associated with a supercell thunderstorm was observed in the adjacent waters of southern China on the evening of 18 April 2019. The case was documented using surface weather observations and Doppler radar data. A weather station near the tornado/waterspout, recorded wind gusts corresponding to hurricane intensity for a few seconds, never observed before in the region. The Doppler velocity associated with the tornado/waterspout was analysed and the vertical profile of the velocity could be very useful for wind engineering applications in the region. Dual‐polarization observations also were analysed and exhibited some similar signatures documented in supercell tornadoes in other parts of the world. Predictability of the tornado/waterspout was studied using a numerical weather prediction model. It showed that the location and timing of the waterspout/tornado could be roughly reproduced, and the model might be used to give earlier alerting to the vessels operating in the south China coastal waters. Abstract : (a) The surface isobaric chart at 12 UTC, 18 April 2018. (b) The sounding at 12 UTC.